Stability Prediction of a Multi Purpose Vessel - Wardhana, Ede Mehta; Soetardjo, Meitha (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
Operational determination requirements for Multi Purpose Vessel Ship need to consider the basic functions carried out, namely to carry out the transportation of equipment and combat logistics from the base to the operating area both in the context of amphibious landings and administration landings. Stability predictions are very important to be carried out at the design stage to determine the static stability conditions of the ship as well as its estimated dynamic stability In addition to the basic functions on board the type of Multi Purpose Vessel (MPV) Ship can be given the following additional functions: Transport troops, logistics and equipment from or ships to landing beaches, and sea transportation assistance, in SAR activities. In this manuscript, the MPV will be analyzed for the stability value. Those stability will be analyzed in order to predict whether the stability value in the MPV for the operational ship is feasible or not. The calculation will take into account the value of KN and also limiting KG value. The result is shown that the overall KN value shows good and normal value for the MPV